PENTINGNYA MENDETEKSI ORAL LEUKOPLAKIA SEBAGAI ORAL POTENTIALLY MALIGNANT DISORDERS (LAPORAN KASUS) - Revi Nelonda; Tenny Setiani Dewi (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2018)
Oral Leukoplakia (OL) is white plaque lesion in oral mucosa that cannot be scraped and one of Oral Potentially Malignant Disorder (OPMD) with incidence about 2.5% of all populations in the world. The most case of oral squamous cell carcinoma are preceded by OPMD. The aim of this case report is to understand the importance of detection oral lesion that could potentially become malignancy. A 28-year-old male patient complained of sores on his tongue that had not healed for 2 months. Intraoral examination obtained red and white lesion on the left lateral tongue: shallow reddish ulcer with irregular border in region 35-36, followed by unscrapable white plaque lesion with slight induration in region 37-38. Hematological examination showed normal range. According anamnesis and clinical examination, diagnosis of traumatic ulcer and OL were made. Patients were treated with multivitamins and antiseptic mouthwash. Histopathological examination results from lesion biopsies show a hyperplastic mass, parakeratosis and a tissue with polymorphic form, a hyperchromatic nucleus of cells associated with histopathologic criteria of squamous cell carcinomas with well differentiation. The patient was referred to the Hemato-oncology Department for chemotherapy. There are two important parameters should be considered when evaluating the potential for malignant change of OL that is when finding white lesions with or without red lesions should always be suspected as OPMD and always confirm it by histopathological examination as early as possible. Accurate examination and histopathologic examination is essential to obtain a good prognosis in OPMD.